Linking people and riparian forests: a sociocultural and ecological approach to plan integrative restoration in farmlands - Lucero, Tania; Ibarra, Jose Tomas; Rojas, Isabel M. (My University, 2024)
Global initiatives to restore habitats aim to improve ecosystem health; however, restoration programs are challenged with balancing human needs with ecological restoration objectives. To advise programs that aim to restore forest in farmlands and complement other analyses on ecologically-based reference sites, we (1) identified species with sociocultural importance, termed as "priority species"; (2) developed an integrative index to find habitats where priority species coincide with healthy ecological conditions (i.e. relatively high diversity, specific plant composition, etc.); and (3) evaluated whether sociodemographic profiles of landowners influenced their plant knowledge and ecological condition of habitats. Our approach was applied to riparian forests in farmlands of the Tolten watershed in southern Chile. We conducted structured interviews to gather information on traditional uses and management of trees in riparian habitats from 45 landowners. We developed an integrative index by combining sociocultural information from interviews with existing vegetation data. From the list of 65 trees provided by landowners, we selected five priority species based on their high saliency, multiple uses, and known management. Only 6 out of 98 sites had high integrative index scores, with the majority showing low values for sociocultural and ecological conditions. Except for a difference in ecological criteria and gender, the evaluation of landowners' knowledge level with sociodemographic profiles did not show significant relationships. These findings suggest that our integrative index can guide the design of restoration objectives, emphasizing on species that are important to local communities by providing information on the ecological conditions in which these plants co-occur.
Keywords: agriculture; forest; local knowledge; policy; social-ecological restoration